Comparing sexual dysfunction in cosmetic rhinoplasty candidates and normal population among married women in Shiraz, Iran: A case-control study - Ali Sahraian; Masoud Janipour; Atoosa Ebrahimi; Zohre Zareizadeh; Pardis Habibi; Amirhossein Babaei (International Journal of Reproductive BioMedicine)
Background: Disturbed self-esteem and self-image can be found in body dysmorphic individuals, and sexual dysfunction is also more frequent among these individuals. Body image concerns may also contribute to the tendency to undergo cosmetic procedures, including rhinoplasty. Objective: This study aimed to compare sexual dysfunction in married women who were candidates for cosmetic rhinoplasty to a control group. Materials and Methods: This case-control study was conducted among 342 married women in Shiraz, Iran, from December 2021–2022. The case group included 192 cosmetic rhinoplasty candidates, and the control group comprised 150 women who were not candidates for cosmetic procedures; they were selected from the ear, nose, and throat outpatient department. Data on demographic features, psycho-social history, and quality of marital life were collected by face-to-face interviews. To evaluate their sexual performance, the participants filled out the female sexual function index questionnaire.